Analisis Aspek Perkembangan Anak Usia Dini dalam Perspektif Agama Islam - Suryani, Yani; Encep Solihutaufa; Aris Gundara; Nani Widianingsih (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This research aims to analyze aspects of early childhood development from a religious perspective. Early childhood development includes various dimensions, such as physical, cognitive, social, emotional and spiritual development, all of which interact and influence each other. Religious perspectives play an important role in forming moral, ethical and spiritual values ​​in children from an early age. In this context, religion not only functions as a moral foundation, but also as a guide in forming children's character and identity. This approach sees that child development does not only involve physical and intellectual aspects, but also spiritual aspects related to knowing God, forming morals, and developing emotional and social intelligence within the framework of religious teachings. This research uses a qualitative approach with literature analysis, which examines various references from holy books, opinions of ulama, as well as relevant religious education studies. The research results show that religious education from an early age can accelerate the process of children's moral and spiritual development, improve social skills, and form good character, which will be the foundation for their success in the future.